High velocity oxy-fuel spraying theory, structure-property relationships and applications - Sobolev, V. V. (Maney, 2004)
High Velocity Oxy-Fuel (HVOF) Spraying is widely used now for many industrial applications and is probably the best among the thermal spray techniques for some specific needs, e.g., for deposition of the cement coatings. Both industry and research laboratories have a need to improve their understanding of the HVOF spray processing in order to develop the optimum conditions and effective control of HVOF spraying which enables production of the quality coatings. Addressing this need is the main objective of this book.
Published for the Institute of Materials, Minerals, and Mining.
Keywords: High energy forming.; elektronické knihy; electronic books